2018
DOI: 10.1002/pbc.27412
|View full text |Cite
|
Sign up to set email alerts
|

The role of routine imaging in pediatric cutaneous melanoma

Abstract: Children with spitzoid melanoma require minimal imaging at diagnosis and follow-up. Patients with conventional MM should be imaged according to adult guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…It is difficult to ascertain whether the location of diagnosis and treatment for children and adolescents with malignant melanoma ultimately influences outcome. It is well recognized that children and adolescents diagnosed with cancer benefit from access to a specialized multidisciplinary team with ongoing systematic clinical reviews and surveillance imaging ( 21 , 28 , 29 ). A recent Italian study that analyzed nationwide hospital discharge of adolescents with melanoma found that patients were dispersed across a large number of hospitals, not always in a pediatric oncology center.…”
Section: Discussionmentioning
confidence: 99%
“…It is difficult to ascertain whether the location of diagnosis and treatment for children and adolescents with malignant melanoma ultimately influences outcome. It is well recognized that children and adolescents diagnosed with cancer benefit from access to a specialized multidisciplinary team with ongoing systematic clinical reviews and surveillance imaging ( 21 , 28 , 29 ). A recent Italian study that analyzed nationwide hospital discharge of adolescents with melanoma found that patients were dispersed across a large number of hospitals, not always in a pediatric oncology center.…”
Section: Discussionmentioning
confidence: 99%
“…Given the low risk of spread and recurrence, children with spitzoid melanoma lacking TERT promoter alterations may require minimal imaging (at diagnosis as well as at follow‐up), as shown by a recent pediatric study that compared imaging findings for spitzoid melanoma versus conventional melanoma 38 …”
Section: Diagnostic Workupmentioning
confidence: 99%
“…Given the low risk of spread and recurrence, children with spitzoid melanoma lacking TERT promoter alterations may require minimal imaging (at diagnosis as well as at follow-up), as shown by a recent pediatric study that compared imaging findings for spitzoid melanoma versus conventional melanoma. 38 The staging (and prognosis) of cutaneous melanoma are based on the American Joint Committee on Cancer (AJCC) tumor, node, metastasis (TNM) system (Figure S1), with the N classification including regional lymph nodes and also non-nodal regional disease (satellites, locally recurrent, or in-transit lesions). 39 Melanoma is a multifactorial disease and most cases are sporadic.…”
Section: Diagnostic Workupmentioning
confidence: 99%
“…To the Editor: Halasheh et al describe their experience with 21 pediatric patients with cutaneous melanoma and conclude that “patients with conventional melanoma should be imaged according to adult guidelines.” The authors state that according to the National Cancer Comprehensive Network (NCCN) guidelines, surveillance imaging is “recommended” at 3‐12 month intervals. Readers may mistakenly interpret the authors’ conclusions to mean that most or all pediatric patients with a history of melanoma should undergo surveillance imaging.…”
mentioning
confidence: 99%